Capture of a catabolic plasmid that encodes only 2,4-dichlorophenoxyacetic acid:alpha-ketoglutaric acid dioxygenase (TfdA) by genetic complementation. - Top, E M (1996)
The modular pathway for the metabolism of 2,4-dichlorophenoxyacetic acid (2,4-D) encoded on plasmid pJP4 of Alcaligenes eutrophus JMP134 appears to be an example in which two genes, tfdA and tfdB, have been recruited during the evolution of a catabolic pathway. The products of these genes act to convert 2,4-D to a chloro-substituted catechol that can be further metabolized by enzymes of a modified ortho-cleavage pathway encoded by tfdCDEF. Given that modified ortho-cleavage pathways are comparatively common and widely distributed among bacteria, we sought to determine if microbial populations in soil carry tfdA on plasmid vectors that lack tfdCDEF or tfdB. To capture such plasmids from soil populations, we used a recipient strain of A. eutrophus that was rifampin resistant and carried a derivative of plasmid pJP4 (called pBH501aE) in which the tfdA had been deleted. Upon mating with mixed bacterial populations from soil treated with 2,4-D, transconjugants that were resistant to rifampin yet able to grow on 2,4-D were obtained. Among the transconjugants obtained were clones that contained a ca. 75-kb plasmid, pEMT8. Bacterial hosts that carried this plasmid in addition to pBH501aE metabolized 2,4-D, whereas strains with only pEMT8 did not. Southern hybridization showed that pEMT8 encoded a gene with a low level of similarity to the tfdA gene from plasmid pJP4. Using oligonucleotide primers based on known tfdA sequences, we amplified a 330-bp fragment of the gene and determined that it was 77% similar to the tfdA gene of plasmid pJP4 and 94% similar to tfdA from Burkholderia sp. strain RASC. Plasmid pEMT8 lacked genes that exhibited significant levels of homology to tfdB and tfdCDEF. Moreover, cell extracts from A. eutrophus(pEMT8) cultures did not exhibit TfdB, TfdC, TfdD, and TfdE activities, whereas cell extracts from A. eutrophus(pEMT8)(pBH501aE) cultures did. These data suggest that pEMT8 encodes only tfdA and that this gene can effectively complement the tfdA deletion mutation of pBH501aE.